Perbedaan Hasil Hitung Jumlah Leukosit dengan Modifikasi Air Perasan Jeruk Nipis (Citrus aurantifolia Swingle) dan Asam Cuka sebagai Pengganti Komposisi Larutan Turk - Yuliana Salman; Novita Nadia; Rabiatul Wahidah (Jurnal Kesehatan Indonesia, 2021)
Examination of the leukocyte count is a routine examination to assess the condition of the immune system and inflammation levels in the body. There are two types of examinations to count blood cells, one of which is leukocytes, using manual and automatic methods. Manual examination was carried out by thinning the blood using Turk's reagent. Under certain conditions, Turk reagents are often not available. This study aimed to determine the number of leukocytes with modified lime juice (Citrus aurantifolia Swingle) and vinegar as an alternative to the composition of the Turk solution. This experimental study used a completely randomized design (CRD) consisting of three treatments and five replications. The samples in this study were 5 samples of venous blood from patients in the level three Dr. R. Soeharsono Hospital in Banjarmasin. This study used a simple random sampling. The treatment used in this study was to use Turk rule, lemon juice (Citrus aurantifolia Swingle) with a concentration of 2%, and vinegar with a concentration of 5%. The results of this study showed that there was no difference in the value of the leukocyte count between the Turk solution (control) and the modified treatment of 2% lime juice and 5% vinegar. Based on these results, it can be concluded that 2% lime juice and 5% vinegar can be used as an alternative to Turk's solution.